Customer Acceptance Analysis of Islamic Bank of Indonesia Mobile Banking Using Technology Acceptance Model (TAM) - Wandira, Raju; Fauzi, Ahmad; Azim, Fauzan; Annas, Firdaus (International Journal of Informatics and Information Systems, 2022)
This takes a look at goals to observe the elements that affect clients in the use of BSI`s cellular baking service. These elements are visible from perceived ease of use the software, the perceived usefulness through clients, and the safety supplied on attitudes and intentions in the use of cellular banking applications. The facts became received from a survey that became dispensed to 183 BSI clients with numerous financial and academic levels. The data have been analyzed with the use of Structural Equation Modeling (SEM) with AMOS software. So that effective consequences are received with a full-size impact of the perceived ease and advantages of the use of the BSI cellular banking software at the attitudes and intentions proven through clients. In addition, in phrases of security, it additionally has an effective impact on attitudes in adopting BSI mobile banking. However, the work environment, buddies, and administrative center doesn't have any full-size impact on the advantages of BSI mobile banking.